Membrane potential hyperpolarization: a critical factor in acrosomal exocytosis and fertilization in sperm within the female reproductive tract - Balestrini, Paula A.; Sulzyk, Valeria; Jabloñski, Martina; Schiavi-Ehrenhaus, Liza J.; González, Soledad N.; Ferreira, Juan J.; Gómez-Elías, Matías D.; Pomata, Pablo; Luque, Guillermina M.; Krapf, Dario; Cuasnicu, Patricia S.; Santi, Celia M.; et al. (Frontiers in Cell and Developmental Biology, 2024)
Hyperpolarization of the membrane potential (Em), a phenomenon regulated by SLO3 channels, stands as a central feature in sperm capacitation-a crucial process conferring upon sperm the ability to fertilize the oocyte. In vitro studies demonstrated that Em hyperpolarization plays a pivotal role in facilitating the mechanisms necessary for the development of hyperactivated motility (HA) and acrosomal exocytosis (AE) occurrence. Nevertheless, the physiological significance of sperm Em within the female reproductive tract remains unexplored. As an approach to this question, we studied sperm migration and AE incidence within the oviduct in the absence of Em hyperpolarization using a novel mouse model established by crossbreeding of SLO3 knock-out (KO) mice with EGFP/DsRed2 mice. Sperm from this model displays impaired HA and AE in vitro. Interestingly, examination of the female reproductive tract shows that SLO3 KO sperm can reach the ampulla, mirroring the quantity of sperm observed in wild-type (WT) counterparts, supporting that the HA needed to reach the fertilization site is not affected. However, a noteworthy distinction emerges-unlike WT sperm, the majority of SLO3 KO sperm arrive at the ampulla with their acrosomes still intact. Of the few SLO3 KO sperm that do manage to reach the oocytes within this location, fertilization does not occur, as indicated by the absence of sperm pronuclei in the MII-oocytes recovered postmating. In vitro, SLO3 KO sperm fail to penetrate the ZP and fuse with the oocytes.Collectively, these results underscore the vital role of Em hyperpolarization in AE and fertilization within their physiological context, while also revealing that Em is not a prerequisite for the development of the HA motility, essential for sperm migration through the female tract to the ampulla.